A new telestroke network system in northern area of Okayama prefecture. Issue 2 (4th February 2021) - Sasaki, Ryo; Yamashita, Toru; Omote, Yoshio; Takemoto, Mami; Hishikawa, Nozomi; Yunoki, Taijun; Kobayashi, Kazuki; Sawata, Takashi; Sato, Yuki; Kubota, Junichi; Mizobuchi, Masayuki; Hayashi, Takashi; et al.
Abstract: Background: Telestroke network can provide rapid access to specialized treatment and improves on‐site management of acute stroke patients through the "hub‐and‐spoke" model. In the northern part of Okayama Prefecture, there has been a regional gap of stroke care due to the shortage of stroke specialists and facilities. In addition, due to the novel coronavirus disease 2019 (COVID‐19), it is required to reduce the unnecessary contact with stroke patients from other hospitals. Aim: We organized a novel cost‐free telestroke network with an image and video sharing for neurological diseases in the northern part of Okayama Prefecture to improve the stroke management in the area. Method: We prepared the tablet device on which Skype ® application was installed for each hospital and recruited the patients who visited or hospitalized in the spoke hospitals and were suspected to have some neurological diseases from April 2019 to May 2020. The patient's clinical data were recorded and analyzed. Results: During the study period, 5 patients were recruited including the cases with the initial diagnosis of stroke or brain tumor. Among them, 2 cases were transferred to the hub hospital, 2 cases were transferred to other hospitals, and 1 case was treated on site under specialist's advice. Conclusion: The new telestroke network system may be beneficial for acute stroke management and reducing the unnecessary patient's transfer in the rural area, especially under coexistence with COVID‐19.